2008
DOI: 10.1097/jcp.0b013e31816774de
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PRX-00023, a Novel, Selective Serotonin 1A Receptor Agonist on Measures of Anxiety and Depression in Generalized Anxiety Disorder

Abstract: PRX-00023, a serotonin 1A receptor agonist, was designed to provide high potency and selectivity for its target. To assess the possible therapeutic utility in anxiety, a randomized, double-blind, placebo-controlled trial was conducted in 311 subjects who met the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, for generalized anxiety disorder. All subjects underwent a 1-week placebo run-in and were randomized to receive once-daily capsules containing either PRX-00023 (80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…There are also no recent or active, ongoing studies of other azapirones such as ipsapirone or lesopitron. In terms of non-azapirone 5-HT 1A agonists, PRX-00023 was studied in GAD in a RCT and, despite good tolerability, it did not show separation from placebo on endpoint anxiety (106). Additionally, there are other selective 5-HT 1A partial agonists, such as TGFK08AA, in development for GAD (89), and TGW00AA (FKW00GA) in Phase 2 studies for GAD and SAD (107).…”
Section: Serotonergic Agentsmentioning
confidence: 99%
“…There are also no recent or active, ongoing studies of other azapirones such as ipsapirone or lesopitron. In terms of non-azapirone 5-HT 1A agonists, PRX-00023 was studied in GAD in a RCT and, despite good tolerability, it did not show separation from placebo on endpoint anxiety (106). Additionally, there are other selective 5-HT 1A partial agonists, such as TGFK08AA, in development for GAD (89), and TGW00AA (FKW00GA) in Phase 2 studies for GAD and SAD (107).…”
Section: Serotonergic Agentsmentioning
confidence: 99%
“…Á Propranolol did not show sufficient evidence in GAD (Meibach et al 1987)(E). Á PRX-00023, a 5-HT 1A receptor agonist, failed to show superiority over placebo (Rickels et al 2008) (E).…”
Section: )(D)mentioning
confidence: 99%
“…tolerability or efficacy) is in the degree of partial agonism: buspirone has ~50% the agonist activity of the natural ligand (serotonin), whereas gepirone has ~80% agonist activity [10]. A recent 8-week double blind placebo-controlled study reported the effects of PRX-00023, a non-azapirone 5HT1A partial agonist with high (~90% intrinsic activity) in GAD [11]. PRX-00023 produced a 9.8 point reduction in HAM-A scores, whereas an 8.5 point reduction was noted in the placebo arm.…”
Section: Serotonin 1a Receptor Partial Agonistsmentioning
confidence: 97%